Interfacial arrangement and phase transitions of PNiPAm microgels with different crosslinking densities - Rey, Marcel; Hou, Xunan; Tang, Jo Sing; Vogel, Nicolas (Soft Matter, 2017)
Microgels are colloidal hydrogel particles that exhibit a pronounced softness, which arises from the swollen nature of the constituent polymer network. This softness leads to a substantial deformability of such particles at liquid interfaces, which, in turn translates into a complex phase behaviour that can exhibit a phase transition between a non-close packed and a close packed arrangement. Here, we explore how the degree of swellability and deformability - and therefore the softness of the particles - affects the phase behaviour of microgels at the air/water interface upon compression. We use precipitation polymerization to synthesize poly(N-isopropylacrylamide) microgels with similar hydrodynamic radii in the collapsed state and systematically vary the degree of swellability by changing the crosslinking density. We spread these microgels onto the air/water interface of a Langmuir trough and characterize their interfacial properties by surface pressure - area isotherms. Furthermore, we continuously transfer the interfacial microgel monolayer during compression onto a solid substrate, thus encoding the complete phase diagram of the microgels with increasing particle density as a function of the position on the solid substrate. We investigate the microgel arrangement by atomic force microscopy and scanning electron microscopy and use image analysis to extract quantitative information on the interparticle distance and degree of order. We find that the phase transition is very sensitive to the crosslinking density and occurs at much lower surface pressures for less deformable particles. The softest microgels do not undergo any phase transition. Instead, the system exhibits pronounced local conformation changes around point defects with local five- and sevenfold symmetries, indicating that the geometry of the assembled structure effectively controls the local pressure experienced by the microgels.

Surface Patterning with SiO2@PNiPAm Core–Shell Particles - Tang, Jo Sing; Bader, Romina Sigrid; Görlitzer, Eric; Wendisch, Jan Fedja; Bourret, Gilles Remi; Rey, Marcel; Vogel, Nicolas (ACS Omega, 2018)
Colloidal lithography is a cost-efficient method to produce large-scale nanostructured arrays on surfaces. Typically, colloidal particles are assembled into hexagonal close-packed monolayers at liquid interfaces and deposited onto a solid substrate. Many applications, however, require non close-packed monolayers, which are more difficult to fabricate. Preassembly at the oil/water interface provides non close-packed colloidal assemblies but these are difficult to transfer to a solid substrate without compromising the ordering due to capillary forces acting upon drying. Alternatively, plasma etching can reduce a close-packed monolayer into a non close-packed arrangement, however, with limited interparticle distance and compromised particle shape. Here, we present a simple alternative approach toward non close-packed colloidal monolayers with tailored interparticle distance, high order, and retained spherical particle shape. We preassemble poly(N-isopropylacrylamide)-silica (SiO2@PNiPAm) core–shell particles at the air/water interface, transfer the interfacial spacer to a solid substrate, and use the polymer shell as a sacrificial layer that can be thermally removed to leave a non close-packed silica monolayer. The shell thickness, cross-linking density, and the phase behavior upon compression of these complex particles at the air/water interface provide parameters to precisely control the lattice spacing in these surface nanostructures. We achieve hexagonal non close-packed arrays of silica spheres with interparticle distances between 400 and 1280 nm, up to 8 times their diameter. The retained spherical shape is advantageous for surface nanostructuring, which we demonstrate by the fabrication of gold nanocrescent arrays via colloidal lithography and silicon nanopillar arrays via metal-assisted chemical etching.<br